2016
DOI: 10.1016/j.bpj.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of RyR2 Has a Biphasic Effect on the Threshold for Store Overload-Induced Calcium Release

Abstract: At the single-channel level, oxidation of the cardiac ryanodine receptor (RyR2) is known to activate and inhibit the channel depending on the level of oxidation. However, the mechanisms through which these changes alter the activity of RyR2 in a cellular setting are poorly understood. In this study, we determined the effect of oxidation on a common form of RyR2 regulation; store overload-induced Ca(2+) release (SOICR). We found that oxidation resulted in concentration and time-dependent changes in the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Our previous work studying the effect of caffeine and oxidation has shown that a common mechanism by which the propensity of SOICR is increased is due to a reduction in the F SOICR (Kong et al ., ; Waddell et al ., ). Therefore, we next explored the effect of class I and class II kinase inhibitors on F SOICR (which is expressed as a percentage of the total store) using the luminally expressed Ca 2+ sensor D1ER as previously described (Jones et al ., ; Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Our previous work studying the effect of caffeine and oxidation has shown that a common mechanism by which the propensity of SOICR is increased is due to a reduction in the F SOICR (Kong et al ., ; Waddell et al ., ). Therefore, we next explored the effect of class I and class II kinase inhibitors on F SOICR (which is expressed as a percentage of the total store) using the luminally expressed Ca 2+ sensor D1ER as previously described (Jones et al ., ; Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Class I kinase inhibitors increase the propensity for SOICR HEK293 cells expressing RyR2 have been well established to display SOICR with very similar characteristics to cardiac cells (Zhang et al, 2014;Waddell et al, 2016). In this study, HEK293 cells expressing RyR2 were used to investigate the impact of class I and II kinase inhibitors on the occurrence of SOICR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations